Part II of Finnish Agility Dog Survey: Agility-Related Injuries and Risk Factors for Injury in Competition-Level Agility Dogs - Leena Inkilä; Heli K. Hyytiäinen; Anna Hielm-Björkman; Jouni Junnila; Anna Bergh; Anna Boström (Animals, 2022)
Dog agility is associated with a risk for sport-related injuries, but few risk factors for injury are known. A retrospective online questionnaire was used to collect data on 864 Finnish competition-level agility dogs—including 119 dogs (14%) with agility-related injury during 2019. Data included injury details, health background, experience in agility, and sport and management routines prior to the injury. Risk factors for injury were evaluated with multivariate logistic regression. The rate of competition-related injuries was 1.44 injuries/1000 competition runs. The front limb was injured in 61% of dogs. In 65% of dogs, the injury presented as lameness. The main risk factors for agility-related injury during 2019 were multiple previous agility-related injuries (OR 11.36; 95% CI 6.10–21.13), older age when starting course-like training (OR 2.04 per one year increase; 95% CI 1.36–3.05), high training frequency, diagnosis of lumbosacral transitional vertebra, and physiotherapy every two to three months compared with never. The most important protective factors were moderate competition frequency and A-frame performance technique. These associations do not confirm causality. We identified new risk factors for injury in agility. This information can be used to improve the welfare of agility dogs.